2010
DOI: 10.1007/s10152-010-0227-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of oogenesis in imposex females of Babylonia areolata (Caenogastropoda: Buccinidae)

Abstract: During a tributyltin (TBT)-exposure experiment, the ultrastructural features of oogenesis have been examined in TBT-induced imposex females of Babylonia areolata and compared with those of the normal female. The results obtained from such experiment demonstrates that B. areolata exhibits a low to moderate intensity of imposex because all VDSI values are never higher than 3. Ultrastructures of germ cell development including oogonia, pre-vitellogenic, early vitellogenic, late vitellogenic and mature oocytes sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Imposex-affected females of many species (e.g., Bolinus brandaris Ramón and Amor 2001; Buccinum undatum Mensink et al 2002;Rapana venosa Mann et al 2006) present a normal histological structure of the ovary. Also, similarities in the ultrastructure of oogenesis between not severely imposex-affected and normal females have been reported, for example, in Hexaplex trunculus (Axiak et al 2003) and Babylonia areolata (Muenpo et al 2011). Imposex has been found to alter the reproductive function by blocking the pallial part of the oviduct; when this occurs, ova cannot be laid and females are effectively sterilized (e.g., Nucella lapillus; Gibbs and Bryan 1986;Gibbs et al 1987), or copulation is prevented due to the opening of the bursa copulatrix (e.g., Ocenebra erinacea Gibbs et al 1990;Oehlmann et al 1992; Hexaplex trunculus Axiak et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Imposex-affected females of many species (e.g., Bolinus brandaris Ramón and Amor 2001; Buccinum undatum Mensink et al 2002;Rapana venosa Mann et al 2006) present a normal histological structure of the ovary. Also, similarities in the ultrastructure of oogenesis between not severely imposex-affected and normal females have been reported, for example, in Hexaplex trunculus (Axiak et al 2003) and Babylonia areolata (Muenpo et al 2011). Imposex has been found to alter the reproductive function by blocking the pallial part of the oviduct; when this occurs, ova cannot be laid and females are effectively sterilized (e.g., Nucella lapillus; Gibbs and Bryan 1986;Gibbs et al 1987), or copulation is prevented due to the opening of the bursa copulatrix (e.g., Ocenebra erinacea Gibbs et al 1990;Oehlmann et al 1992; Hexaplex trunculus Axiak et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified OTs in water, crop, and food at concentrations that may be highly toxic to aquatic creatures and carcinogenic to humans (Muenpo, Suwanjarat, & Klepal;Guðmundsdóttir, Ho, Lam, Svavarsson, & Leung, 2011;Ho & Leung, 2014). Therefore, many countries and organizations have established maximum limit standards for OTs.…”
Section: Introductionmentioning
confidence: 99%
“…Neogastropod species have been repeatedly identified as suitable pollution indicators mainly related to organotin compounds (from paints used on commercial vessels and ports as biocides), which induce masculinization in females (imposex) (e.g. Bryan et al 1988;Oehlmann et al 1991;Nias et al 1993;Shim et al 2000;Muenpo et al 2011). A common manifestation of imposex in females is the presence of a penis, whose length has been correlated with the concentrations of butyltins in the environment (Mensink et al 1996;Tosten et al 2013).…”
Section: Introductionmentioning
confidence: 99%